Species of Psilocybe (Hymenogastraceae) from Yunnan, southwest China - Ma, Tao; Ling, Xiao-Fei; Hyde, Kevin D. (Phytotaxa, 2016)
Species of Psilocybe collected in Yunnan Province in southwest China were identified using both morphological characteristics and phylogenetic analyses of ITS and nrLSU sequence data. Six phylogenetic species were recognized among the studied collections. In this paper, Psilocybe ruliensis is introduced as a new species, while Psilocybe keralensis is new to China, P. aff. fasciata is new to Yunnan and P. chuxiongensis is recollected in Yunnan Province. The remaining two phylogenetic species are not described or detailed due to the paucity of the material. The four species appear to be endemic to Asia.